The pro-invasive factor COL6A2 serves as a novel prognostic marker of glioma - Zhu, Jinchao; Lin, Qingyuan; Zheng, Haiyan; Rao, Yamin; Ji, Tianhai (Frontiers in Oncology, 2022)
Background: Glioma is an incurable malignant lesion with poor outcome characterized by easy recurrence after surgery with or without radiotherapy and chemotherapy. Studies have shown that COL6A2 is closely related to the tumorigenesis and development of a variety of tumors. However, the role of COL6A2 in glioma and the relationship between COL6A2 and tumor infiltrating immune cells remain unclear. Methods: Western blot, real-time PCR, a tissue microarray and immunohistochemistry were applied to detect COL6A2 mRNA and protein amounts in glioma. A tissue microarray of glioma samples was used for prognostic analysis. Based on the mRNA expression of COL6A2, patients with glioma in TCGA were divided into the low and high COL6A2 expression groups, and GO and KEGG pathway analyses were performed. A PPI network was constructed using STRING, and the associations of COL6A2 with tumor-infiltrating immune cells and immune genes were analyzed in the CIBERSORT and TISIDB databases. Results: COL6A2 mRNA and protein amounts were increased in glioma. Multiple-database and tissue microarray analyses showed that COL6A2 expression in glioma was associated with poor prognosis. The mRNA expression of COL6A2 was involved in 22 KEGG pathways, and GSEA analysis showed that 28 and 57 gene sets were significantly enriched at nominal p values <0.01 and <0.05, respectively，protein network revealed a tight interaction between COL6A2 and SPARC. The CIBERSORT database indicated that COL6A2 was correlated with 15 types of tumor-infiltrating immune cells, including M2 macrophages, CD8 T cells, neutrophils, gamma delta T cells, activated CD4 memory T cells, follicular helper T cells, M0 macrophages, M1 macrophages, regulatory T cells (Tregs), activated NK cells, eosinophils, activated mast cells, monocytes, activated dendritic cells, and resting CD4 memory T cells. The TISIDB database indicated that COL6A2 was significantly correlated with lymphocytes such as regulatory T cell, Type 17 T helper cell, Type 1 T helper cell, and immunomodulatory genes. Conclusions: COL6A2 may be a novel potential prognostic biomarker of glioma and associated with tumor-infiltrating immune cells in the tumor microenvironment, which suggests COL6A2 as a potential target for future treatment.